2012
DOI: 10.1073/pnas.1109370109
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic reciprocity of sodium and potassium channel expression in a macromolecular complex controls cardiac excitability and arrhythmia

Abstract: The cardiac electrical impulse depends on an orchestrated interplay of transmembrane ionic currents in myocardial cells. Two critical ionic current mechanisms are the inwardly rectifying potassium current (I K1 ), which is important for maintenance of the cell resting membrane potential, and the sodium current (I Na ), which provides a rapid depolarizing current during the upstroke of the action potential. By controlling the resting membrane potential, I K1 modifies sodium channel availability and therefore, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
196
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 183 publications
(210 citation statements)
references
References 35 publications
13
196
0
1
Order By: Relevance
“…6, A and B). This is consistent with observations from other groups who have found that I Na-P density increases in the presence of Kir2.1 (19). F97C-CAV3 increased I Na-L but did not affect I Na-P in both I K1 -enhanced and iPS-CMs.…”
Section: H1615 Ips-cm Model For Investigating Complex Inherited Arrhysupporting
confidence: 82%
See 1 more Smart Citation
“…6, A and B). This is consistent with observations from other groups who have found that I Na-P density increases in the presence of Kir2.1 (19). F97C-CAV3 increased I Na-L but did not affect I Na-P in both I K1 -enhanced and iPS-CMs.…”
Section: H1615 Ips-cm Model For Investigating Complex Inherited Arrhysupporting
confidence: 82%
“…iPS-CM MODEL FOR INVESTIGATING COMPLEX INHERITED ARRHYTHMIAS ability and may increase both peak and late current (1,19). Compared with WT-CAV3, F97C-CAV3-infected iPS-CMs produced an increase in I Na-L without affecting I Na-P .…”
Section: H1618mentioning
confidence: 99%
“…This is derived from this work and recent work by Abriel and colleagues (27), who demonstrated that Na V 1.5 associates with syntrophin and SAP97, Makielski and colleagues (5,23), who established that Na V 1.5 coimmunoprecipitates with Cav3 and syntrophin, Vandenberg and colleagues, who showed that Kir2.1 coimmunoprecipitates with syntrophin (11), and Anumonwo and colleagues (28), who assert that Kir2.1 associates with SAP97. This is also in agreement with a recent study by Jalife and colleagues (29), who propose reciprocal modulation of Kir2.1 and Na V 1.5 and suggest that these ion channels are in the same macromolecular complex. Although these protein interactions have been shown separately, our findings corroborate these studies, and we demonstrate here pathophysiologic consequences of the association of Cav3 with Kir2.1 and Na V 1.5.…”
Section: Mechanism Of the Effect Of Lqt9 Cav3supporting
confidence: 82%
“…The INa-IK1 ion channels form one such complex, recently shown to control cardiac excitability and arrhythmia by Milstein et al [8]. Their inter-species study concluded that an increase in functional expression of one channel reciprocally modulates the expression of the other to maximise cardiac excitability.…”
Section: Introductionmentioning
confidence: 99%